Synovial macrophage-osteoclast differentiation in inflammatory arthritis. Issue 10 (1st October 2002) - Danks, L; Sabokbar, A; Gundle, R; Athanasou, N A
Abstract : Background: Pathological bone resorption (marginal erosions and juxta-articular osteoporosis) by osteoclasts commonly occurs in rheumatoid arthritis (RA). Objectives: To define the nature of the mononuclear precursor cells from which osteoclasts are formed in inflamed synovial tissues and to determine the cellular and humoral factors which influence osteoclast differentiation. Method: Macrophage (CD14+), non-macrophage (CD14−), and unsorted (CD14+/CD14−) synovial cell populations from RA and inflammatory/non-inflammatory osteoarthritis (OA) synovium were cultured in the presence of receptor activator for nuclear factor κB ligand (RANKL) and monocyte-colony stimulating factor (M-CSF; in the presence/absence of prostaglandin E2 (PGE2 ), interleukin 1β (IL1β), tumour necrosis factor α (TNFα), and IL6). Osteoclast differentiation was assessed by expression of tartrate resistant acid phosphatase (TRAP), vitronectin receptor (VNR), and lacunar resorption. Results: TRAP+ and VNR+ multinucleated cells capable of lacunar resorption were only formed in cultures of CD14+-containing synovial cell populations (that is, CD14+ and CD14+/CD14− cells). No difference in the extent of osteoclast formation was noted in cultures of CD14+ cells isolated from RA, inflammatory OA, and non-inflammatory OA synovium. However, more TRAP+/VNR+ cells and more lacunar resorption was noted in CD14+/CD14− cells from RA and inflammatory OA synovial tissues. The addition of PGE2, IL1β, TNFα, and IL6 did not increase RANKL/M-CSF-induced osteoclast formation and lacunar resorption of both CD14+/CD14− and CD14+ synovial cell populations. Conclusions: Osteoclast precursors in synovial tissues are CD14+ monocyte/macrophages. The increase in osteoclast formation in cultures of CD14+/CD14− compared with CD14+ synovial cells in RA and inflammatory OA points to a role for CD14− cells in promoting osteoclast differentiation and bone resorption in inflamed synovial tissues by a mechanism which does not involve a direct effect of proinflammatory cytokines/prostaglandins on RANKL-induced macrophage-osteoclast differentiation.